2010
DOI: 10.1007/s10750-010-0436-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of emergent macrophytes to hydrological changes in a shallow lake, with special reference to nutrient cycling

Abstract: The effect of water level reduction on nutrient concentrations and productivity of emergent macrophytes was analyzed in a shallow, polymictic lake, located in Central-Western Poland. The water level was regulated for irrigation purposes from 1974 to 2002, with an average amplitude of 0.85 m. In 2002, the water level was reduced by 0.60 m during winter time and by 0.40 m in summer time. Nutrient concentrations, nitrogen, phosphorus, and potassium standing stocks and aboveground biomass production were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Tian et al (2009) analyzed the reed nutrient uptake in Taihu Lake, China, and found that both plant species and soil substrates could influence nutrient concentrations of water body. Lawniczak et al (2010) studied the effect of water level reduction on nutrient concentrations and productivity of reeds in Niepruszewskie Lake of Poland, and presented that the decrease of water level resulted in a negative effect on reed biomass production and its nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al (2009) analyzed the reed nutrient uptake in Taihu Lake, China, and found that both plant species and soil substrates could influence nutrient concentrations of water body. Lawniczak et al (2010) studied the effect of water level reduction on nutrient concentrations and productivity of reeds in Niepruszewskie Lake of Poland, and presented that the decrease of water level resulted in a negative effect on reed biomass production and its nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be found in shore habitats as well. By contrast, T. angustifolia is usually found in the flooded littoral (average 60 and maximum 130 cm water depth) (Lawniczak et al ., ) because of the high capacity for oxidation in its rhizosphere (Armstrong et al ., ). These results also support the idea of depositional changes in the shore of El Tobar, establishing differences between levels in the bottom (MZ1a dominated by Juncus ) and the uppermost part of the sequence (MZ2b, dominated by Typha ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach makes it possible to evaluate the directionality of changes occurring in natural lakes of the temperate zone in which there are natural fluctuations of water levels. In lakes with significant water level variations, the development of vegetation will depend on their resistance to prolonged periods of drought or flooding [44].…”
Section: Cartographic Analyses In Lake Overgrowthmentioning
confidence: 99%